The construction method for super structure / Nur Amanina Azemi - Azemi, Nur Amanina (Universiti Teknologi Mara, Perak, 2014)
Practical training course is one of core subject in building surveying programmed. All the student must take this course in semester sixth as a last semester in this programmed. They should be choosing any company that to find their place to do practical training same with their programmed. To do the practical training, I was choosing the private company of the SPP Development Sdn. Bhd. This company do the housing, shop lot and apartment development and I was under the construction management. The charge man, Mr. Nik Abdullah Bin Nik Ibrahim as an i.o. (Inspection Officer) for the architecture in the construction site had been appointed to be my supervisor at the construction site during the training. During the practical training, I was exposed to visiting the construction site for apartment and survey the progress of the construction. I‘m also must do the checklist for the construction progress. Practical training will be end after four months the students complete the training. At the last semester before finish this course, the student must be prepared a report according to the topic that they are choose and relevant with their job was they do during practical training.